Place Names in Finland: Settlement History, Sociolinguistics, and the Finnish/Swedish Language Boundary - Embleton, Sheila (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
There is much ongoing research in Sweden and Finland concerned with uncovering settlement history in Finland through the interaction of Swedish and Finnish in place names. The Finnish case is particularly interesting, as the contact extends from prehistoric times through historic times to the present, and as the topic has become relevant to a hot sociolinguistic debate amongst scholars and the lay public alike. This paper presents a classification and exemplification of different types of loan-name found in areas of Finnish—Swedish contact, and shows how place names can provide information on age of settlements and ethnicity of various layers of settlement, using etymology and linguistic methods in conjunction with other tools (e.g., from geology). The linguistic evidence often provides fairly clear answers as to which group was original in a given area, but those answers may not be accepted by current inhabitants for political reasons. Details of the sociolinguistic debate, from both the historical and current points of view, are presented, along with an overview of current scholarly research on the topic.